(untitled) (Research, Society and Development, 2020)
The teaching-learning process is challenging in human anatomy. In this process, practical exams are necessary to enable a proper evaluation of the students. Students’ performance, on the other hand, reflects not only their knowledge but also their individual reactions to exams. Objective: This study aimed to identify signs and symptoms of stress in undergraduate students before practical exams in human anatomy. Methods: The sample consisted of 93 students (48 females and 45 males, mean age = 20.33 years) enrolled in medical and dental courses at undergraduate level. Blood rate, heart rate and oxygen saturation were assessed 30 minutes before the practical exams. Lipp´s Inventory of Stress Symptoms for Adults (LSSI) was used. Results: Statistically significant differences (p < 0.05) was observed for the systolic blood pressure between females (117.76  11.82 mmHg) and males (120.66  10.09 mmHg). Diastolic rate, respiratory rate and oxygen saturation were similar between sex groups (p > 0.05). A higher report of signs and symptoms of stress was detected in females (p < 0.05) for each of the stress stages described by LSSI, namely alarm, resistance and exhaustion. Medical and dental undergraduate students manifested signs and symptoms of stress before practical exams in human anatomy. The outcomes were more evident in females.